Light absorption and heating type regenerated polyester fiber material and preparation method thereof
By introducing hierarchical porous γ-alumina and graphene composite materials and titanium dioxide particles into fiber-grade recycled PET chips, the problems of low resource utilization rate and poor heat conduction of waste textiles are solved, achieving efficient heat conduction and photothermal conversion, and enhancing the strength and self-cleaning properties of the fibers.
Patent Information
- Application Number
- CN202411382595.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-09-30
AI Technical Summary
Existing technologies have low resource utilization rates for waste textiles, poor heat conduction of light-absorbing and heat-generating polyester fiber materials, and insufficient fiber strength and photocatalytic performance.
A layered porous γ-alumina and graphene composite material is used as a thermal conductive material. By melt-blending it with fiber-grade recycled PET chips and combining it with titanium dioxide particles, a fiber material with high-efficiency heat conduction and photocatalytic properties is formed.
It improves the heat conduction efficiency and photothermal conversion efficiency of fiber materials, while enhancing the tensile strength and self-cleaning antibacterial properties of the fibers.
Abstract
Description
Technical Field
[0001] The invention relates to the field of fiber technology, and in particular to a light-absorbing and heat-generating regenerated polyester fiber material and a preparation method thereof. Background Art
[0002] At present, a large amount of waste textiles cannot be recycled, which brings great pressure to the environment. Since the industrial chain of waste textile utilization is still incomplete, the overall recycling efficiency is low. Therefore, it is an important development direction to build a recycling system for waste textiles and improve the resource utilization and high-value utilization of waste textiles. At present, chemical method is the main method for recycling waste cotton and polyester textiles, but there are still problems of low recycling rate and poor product quality.
[0003] At present, the performance research and product development of light-absorbing and heat-generating far-infrared polyester interwoven fabrics have made certain progress. Among them, the 3.33dtex light-absorbing and heat-generating hollow fibers produced on the indirect spinning production line of Toyobo have produced products that meet the requirements by adjusting the melt delivery and heat medium temperature, reducing the initial pressure of the components, and reasonably adjusting the draft ratio. The light-absorbing and heat-generating far-infrared polyester interwoven fabrics have significantly improved heating and heat preservation effects under sunlight and far-infrared lamps, and are used in clothing and textiles that require additional warmth and health care functions. With the development of technology and the increase in market demand, the light-absorbing and heat-generating polyester fiber materials need to be further expanded.
[0004] Chinese patent application number 201910951301.5, the name of the invention patent is a modified polyester fiber and a preparation method. The application discloses a modified polyester fiber and a preparation method. The coating includes two components, and the modified polyester fiber includes: the modified polyester fiber includes functional particles with a core-shell structure, wherein the core of the functional particles is a light-absorbing and heat-generating particle, and the shell of the functional particles is a light-transmitting layer. Since it includes functional particles with a core-shell structure, and the core of the functional particles is a light-absorbing and heat-generating particle, and the shell is a light-transmitting layer, when the fabric made of the modified polyester fiber is irradiated with light, the light can pass through the light-transmitting layer, and the light-absorbing and heat-generating particles absorb the light and convert it into heat, thereby providing a warming effect. However, the functional particles with a core-shell structure prepared by the invention do not have the function of conducting heat to the inside of the shell to store heat.
[0005] Therefore, in view of this, the inventor has studied and improved the existing technology and its deficiencies, and provided a light-absorbing and heat-generating regenerated polyester fiber material and a preparation method thereof, in order to achieve a more practical purpose. Summary of the invention
[0006] In order to solve the problems mentioned in the above background technology, the present invention provides a light-absorbing and heat-generating regenerated polyester fiber material and a preparation method thereof.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions:
[0008] A method for preparing a light-absorbing and heat-generating regenerated polyester fiber material comprises the following steps:
[0009] S1, breaking the recycled plastic bottles into small pieces, using ethylene glycol as a reaction medium for depolymerization to obtain dimethyl terephthalate and ethylene glycol, carrying out an ester exchange reaction between dimethyl terephthalate and methanol, and then polymerizing the reaction to prepare fiber-grade recycled PET chips;
[0010] S2, using a mixed aqueous solution of aluminum isopropoxide, acetic acid and polyvinyl alcohol as a precursor solution, preparing a hybrid hierarchical porous material by freeze-drying technology, and then calcining at high temperature to remove organic matter, and finally obtaining a hierarchical porous γ-type alumina;
[0011] S3, immersing the hierarchical porous γ-alumina in a solution containing graphene, and uniformly dispersing the graphene into the pores of the hierarchical porous γ-alumina by ultrasonic dispersion or high shear stirring to obtain a graphene-doped porous γ-alumina composite material, and then heat treating the graphene-doped porous γ-alumina composite material;
[0012] S4, adding a modifier to a urea-formaldehyde resin precursor solution, heating and stirring for 30-45 minutes, then adding a certain mass fraction of a porous γ-alumina composite material doped with graphene, and using a mechanical stirrer to stir the solution at a speed of 300 to 2000 rpm for 30-60 minutes to obtain a uniformly dispersed precursor mixed solution;
[0013] S5, heating paraffin to a molten state and mixing it with the precursor mixed solution, adding an emulsifier and using a mechanical stirrer to form an emulsion, continuing to adjust the pH value by adding citric acid, heating the reaction system, and stirring the mechanical stirrer at a speed of 600-700 rpm for 110min-125min to obtain a micropolymer, wherein the weight ratio of paraffin, emulsifier, and citric acid is, then adding sodium hydroxide solution to adjust the pH value to neutral, terminating the reaction, and finally filtering the micropolymer, and washing the micropolymer with deionized water several times, and then drying it at room temperature for standby use;
[0014] S6, heating the PET chips to a molten state, and performing surface modification on the micropolymer to make the micropolymer compatible with the PET chips to form a molten mixture, filtering the molten mixture through a filter and cooling it to a temperature suitable for spinning to form a spinning solution, and then obtaining fibers by wet spinning.
[0015] The graphene-doped porous gamma-alumina composite material of the present invention is used as a heat-conducting material for fibers and can provide an efficient heat transfer channel so that heat energy can be transferred to the interior of the micropolymer.
[0016] Preferably, the urea-formaldehyde resin precursor solution is prepared by dissolving urea and a 37% formaldehyde solution in a reactor, and the modifier is melamine.
[0017] Furthermore, the urea-formaldehyde resin precursor solution is prepared by adding triethanolamine to adjust the pH value of the solution.
[0018] As a preferred solution of the present invention, the weight ratio of graphene and hierarchical porous γ-alumina in step S3 is (1-3): (110-180).
[0019] Preferably, the graphene solution in S3 is prepared by the following steps:
[0020] (1) oxidizing graphite by the Hummers method to obtain graphene oxide;
[0021] (2) removing oxygen-containing groups of graphene oxide by chemical reduction to obtain reduced graphene oxide;
[0022] (3) The reduced graphene oxide powder is added to a solvent and subjected to a long-term ultrasonic treatment using an ultrasonic processor.
[0023] Preferably, the mass fraction of the graphene-doped porous γ-alumina composite material relative to the micropolymer is 1%-8%.
[0024] Preferably, in step S5, the weight ratio of paraffin wax, emulsifier and citric acid is (20-40): (3-10): (0.3-1.8).
[0025] Preferably, the paraffin is replaced by one or more of nano zirconium carbide, polyethylene glycol, hydrocarbon wax, and carbon nanotubes.
[0026] Preferably, the molten mixture filtered in step S6 is melted by a screw extruder and quantitatively fed into a spinning assembly through a spinning pump, and then extruded from the capillaries of the spinneret to form liquid filaments, which are then cooled and formed, stretched into filaments at high speed by a winding device, and then heat-set to obtain fibers.
[0027] Preferably, the fiber-grade recycled PET chips in step S6 are melt-blended with titanium dioxide and then combined with the micropolymer.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] 1. The porous structure of hierarchical porous γ-alumina is used in the present invention to provide mechanical support for graphene bonding. Graphene is filled into the pores of the hierarchical porous γ-alumina and then mixed with a urea-formaldehyde resin precursor solution to which a modifier is added, so that it serves as the shell of the micropolymer. The porous γ-alumina composite material doped with graphene enhances the heat conduction and absorption rate.
[0030] 2. The present invention adopts melt blending of titanium dioxide and fiber-grade recycled PET slices, so that the titanium dioxide particles and the fiber-grade recycled PET slices form a bonding force. The titanium dioxide particles evenly distributed on the fiber-grade recycled PET slices can not only exert the light absorption and heat generation function of the photothermal powder, but also improve the tensile strength and modulus of the fiber-grade recycled PET slices. At the same time, the high catalytic activity of the titanium dioxide particles makes it have photocatalytic properties in the PET composite material, which can catalyze chemical reactions under light, and contribute to the self-cleaning and antibacterial properties of the fiber material surface. DETAILED DESCRIPTION
[0031] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] Unless otherwise specified, the raw materials used in the present invention are all conventional products purchased from the market, and some of the raw materials can be obtained by oneself.
[0033] Preparation Example 1
[0034] The preparation of fiber-grade recycled PET chips specifically includes the following steps:
[0035] (1) crushing the recycled plastic bottles into small pieces, and using ethylene glycol as an alcoholysis agent to alcoholyze them into terephthalic acid and ethylene glycol;
[0036] (2) mixing dimethyl terephthalate with methanol, and adding a catalyst, such as tetrabutyl titanate (Ti(OBu)4) or an antimony compound, to the reaction mixture to promote the transesterification reaction;
[0037] (3) Dimethyl phthalate reacts with methanol at high temperature. The methyl formate generated during the reaction can be removed from the reaction system by distillation or other methods to promote the reaction to produce PET monomers.
[0038] (4) When the desired conversion rate is reached, the reaction is stopped and ethylene terephthalate is separated from the mixture by distillation or other separation techniques. The ethylene terephthalate is then purified and subjected to the next polymerization reaction to produce fiber-grade recycled PET chips.
[0039] Example 1
[0040] A method for preparing a light-absorbing and heat-generating regenerated polyester fiber material comprises the following steps:
[0041] S1, breaking the recycled plastic bottles into small pieces, using ethylene glycol as a reaction medium for depolymerization to obtain dimethyl terephthalate and ethylene glycol, carrying out an ester exchange reaction between dimethyl terephthalate and methanol, and then polymerizing the reaction to prepare fiber-grade recycled PET chips;
[0042] S2, using a mixed aqueous solution of aluminum isopropoxide, acetic acid and polyvinyl alcohol as a precursor solution, preparing a hybrid hierarchical porous material by freeze-drying technology, and then calcining at 1100° C. to remove organic matter, and finally obtaining a hierarchical porous γ-type alumina;
[0043] S3, immersing the hierarchical porous γ-alumina in a solution containing graphene, and uniformly dispersing the graphene into the pores of the porous γ-alumina by ultrasonic dispersion or high shear stirring to obtain a porous γ-alumina composite material doped with graphene, and then heat treating the porous γ-alumina composite material doped with graphene;
[0044] S4, dissolving urea and a 37% formaldehyde solution in a reactor and adding melamine, heating and stirring for 30 minutes, then adding 1% by mass of a graphene-doped porous γ-alumina composite material, and stirring the solution at a speed of 800 rpm for 45 minutes using a mechanical stirrer to obtain a uniformly dispersed precursor mixed solution;
[0045] S5, heating paraffin to a molten state and mixing it with the precursor mixed solution, and using an emulsifier and a mechanical stirrer to form an emulsion, continuing to adjust the pH value by adding citric acid, heating the reaction system, and stirring the mechanical stirrer at a speed of 600 rpm for 110 min to obtain a micropolymer, wherein the weight ratio of paraffin, emulsifier, and citric acid is 20:3:0.3, then adding sodium hydroxide solution to adjust the pH value to neutral, terminating the reaction, and finally filtering the micropolymer, and washing the micropolymer with deionized water several times, and then drying it at room temperature for standby use;
[0046] S6. The PET chips are heated to a molten state, and the micropolymer is surface-modified to make the micropolymer compatible with the PET chips. The micropolymer and the PET chips are mixed in a ratio of 8:1 to form a molten mixture. The molten mixture is filtered through a filter and then cooled to a temperature suitable for spinning to form a spinning solution, which is then wet-spun to obtain fibers.
[0047] Example 2
[0048] A method for preparing a light-absorbing and heat-generating regenerated polyester fiber material comprises the following steps:
[0049] S1, breaking the recycled plastic bottles into small pieces, using ethylene glycol as a reaction medium for depolymerization to obtain dimethyl terephthalate and ethylene glycol, carrying out an ester exchange reaction between dimethyl terephthalate and methanol, and then polymerizing the reaction to prepare fiber-grade recycled PET chips;
[0050] S2, using a mixed aqueous solution of aluminum isopropoxide, acetic acid and polyvinyl alcohol as a precursor solution, preparing a hybrid hierarchical porous material by freeze-drying technology, and then calcining at a high temperature of 1100° C. to remove organic matter, and finally obtaining a hierarchical porous γ-type alumina;
[0051] S3, immersing the hierarchical porous γ-alumina in a solution containing graphene, and uniformly dispersing the graphene into the pores of the porous γ-alumina by ultrasonic dispersion or high shear stirring to obtain a porous γ-alumina composite material doped with graphene, and then heat treating the porous γ-alumina composite material doped with graphene;
[0052] S4, dissolving urea and a 37% formaldehyde solution in a reactor and adding melamine, heating and stirring for 30 minutes, then adding 4% by mass of a graphene-doped porous γ-alumina composite material, and using a mechanical stirrer to stir the solution at a speed of 1000 rpm for 40 minutes to obtain a uniformly dispersed precursor mixed solution;
[0053] S5, heating paraffin to a molten state and mixing it with the precursor mixed solution, and using an emulsifier and a mechanical stirrer to form an emulsion, continuing to adjust the pH value by adding citric acid, heating the reaction system, and stirring the mechanical stirrer at a speed of 600 rpm for 110 min to obtain micropolymers, then adding sodium hydroxide solution to adjust the pH value to neutral, terminating the reaction, and finally filtering the micropolymers, washing the micropolymers with deionized water for several times, and then drying them at room temperature for standby use;
[0054] S6. Fiber-grade recycled PET chips are melt-blended with titanium dioxide to form a blended melt, and the micropolymer is surface-modified to make the micropolymer compatible with the blended melt. The micropolymer and PET chips are mixed in a ratio of 8:1 to form a molten mixture. The molten mixture is filtered through a filter and then cooled to a temperature suitable for spinning to form a spinning solution, which is then wet-spun to obtain fibers.
[0055] Example 3
[0056] A method for preparing a light-absorbing and heat-generating regenerated polyester fiber material comprises the following steps:
[0057] S1, breaking the recycled plastic bottles into small pieces, using ethylene glycol as a reaction medium for depolymerization to obtain dimethyl terephthalate and ethylene glycol, carrying out an ester exchange reaction between dimethyl terephthalate and methanol, and then polymerizing the reaction to prepare fiber-grade recycled PET chips;
[0058] S2, using a mixed aqueous solution of aluminum isopropoxide, acetic acid and polyvinyl alcohol as a precursor solution, preparing a hybrid hierarchical porous material by freeze-drying technology, and then calcining at a high temperature of 1100° C. to remove organic matter, and finally obtaining a hierarchical porous γ-type alumina;
[0059] S3, immersing the hierarchical porous γ-alumina in a solution containing graphene, and uniformly dispersing the graphene into the pores of the porous γ-alumina by ultrasonic dispersion or high shear stirring to obtain a porous γ-alumina composite material doped with graphene, and then heat treating the porous γ-alumina composite material doped with graphene;
[0060] S4, dissolving urea and a 37% formaldehyde solution in a reactor and adding melamine, heating and stirring for 30 minutes, then adding 4% by mass of a graphene-doped porous γ-alumina composite material, and using a mechanical stirrer to stir the solution at a speed of 1000 rpm for 40 minutes to obtain a uniformly dispersed precursor mixed solution;
[0061] S5, heating paraffin to a molten state and mixing it with the precursor mixed solution, and using an emulsifier and a mechanical stirrer to form an emulsion, continuing to adjust the pH value by adding citric acid, heating the reaction system, and stirring the mechanical stirrer at a speed of 600 rpm for 120 min to obtain micropolymers, then adding sodium hydroxide solution to adjust the pH value to neutral, terminating the reaction, and finally filtering the micropolymers, washing the micropolymers with deionized water for several times, and then drying them at room temperature for standby use;
[0062] S6. The PET chips are heated to a molten state, and the micropolymer is surface-modified to make the micropolymer compatible with the PET chips. The micropolymer and the PET chips are mixed in a ratio of 8:1 to form a molten mixture. The molten mixture is filtered through a filter and then cooled to a temperature suitable for spinning to form a spinning solution, which is then wet-spun to obtain fibers.
[0063] Example 4
[0064] A method for preparing a light-absorbing and heat-generating regenerated polyester fiber material comprises the following steps:
[0065] S1, breaking the recycled plastic bottles into small pieces, using ethylene glycol as a reaction medium for depolymerization to obtain dimethyl terephthalate and ethylene glycol, carrying out an ester exchange reaction between dimethyl terephthalate and methanol, and then polymerizing the reaction to prepare fiber-grade recycled PET chips;
[0066] S2, using a mixed aqueous solution of aluminum isopropoxide, acetic acid and polyvinyl alcohol as a precursor solution, preparing a hybrid hierarchical porous material by freeze-drying technology, and then calcining at high temperature to remove organic matter, and finally obtaining a hierarchical porous γ-type alumina;
[0067] S3, immersing the hierarchical porous γ-alumina in a solution containing graphene, and uniformly dispersing the graphene into the pores of the porous γ-alumina by ultrasonic dispersion or high shear stirring to obtain a porous γ-alumina composite material doped with graphene, and then heat treating the porous γ-alumina composite material doped with graphene;
[0068] S4, adding a modifier to a urea-formaldehyde resin precursor solution, heating and stirring for 40 minutes, then adding 6% by mass of a porous γ-alumina composite material doped with graphene, and using a mechanical stirrer to stir the solution at a speed of 1200 rpm for 50 minutes to obtain a uniformly dispersed precursor mixed solution;
[0069] S5, heating paraffin to a molten state and mixing it with the precursor mixed solution, and using an emulsifier and a mechanical stirrer to form an emulsion, continuing to adjust the pH value by adding citric acid, heating the reaction system, and stirring the mechanical stirrer at a speed of 650 rpm for 115 min to obtain micropolymers, then adding sodium hydroxide solution to adjust the pH value to neutral, terminating the reaction, and finally filtering the micropolymers, washing the micropolymers with deionized water for several times, and then drying them at room temperature for standby use;
[0070] S6. The PET chips are heated to a molten state, and the micropolymer is surface-modified to make the micropolymer compatible with the PET chips. The micropolymer and the PET chips are mixed in a ratio of 8:1 to form a molten mixture. The molten mixture is filtered through a filter and then cooled to a temperature suitable for spinning to form a spinning solution, which is then wet-spun to obtain fibers.
[0071] Example 5
[0072] A method for preparing a light-absorbing and heat-generating regenerated polyester fiber material comprises the following steps:
[0073] S1, breaking the recycled plastic bottles into small pieces, using ethylene glycol as a reaction medium for depolymerization to obtain dimethyl terephthalate and ethylene glycol, carrying out an ester exchange reaction between dimethyl terephthalate and methanol, and then polymerizing the reaction to prepare fiber-grade recycled PET chips;
[0074] S2, using a mixed aqueous solution of aluminum isopropoxide, acetic acid and polyvinyl alcohol as a precursor solution, preparing a hybrid hierarchical porous material by freeze-drying technology, and then calcining at high temperature to remove organic matter, and finally obtaining a hierarchical porous γ-type alumina;
[0075] S3, immersing the hierarchical porous γ-alumina in a solution containing graphene, and uniformly dispersing the graphene into the pores of the porous γ-alumina by ultrasonic dispersion or high shear stirring to obtain a porous γ-alumina composite material doped with graphene, and then heat treating the porous γ-alumina composite material doped with graphene;
[0076] S4, adding a modifier to a urea-formaldehyde resin precursor solution, heating and stirring for 40 minutes, then adding 8% by mass of a porous γ-alumina composite material doped with graphene, and stirring the solution at a speed of 1400 rpm for 50 minutes using a mechanical stirrer to obtain a uniformly dispersed precursor mixed solution;
[0077] S5, heating paraffin to a molten state and mixing it with the precursor mixed solution, and using an emulsifier and a mechanical stirrer to form an emulsion, continuing to adjust the pH value by adding citric acid, heating the reaction system, and stirring the mechanical stirrer at a speed of 650 revolutions for 120 minutes to obtain micropolymers, then adding sodium hydroxide solution to adjust the pH value to neutral, terminating the reaction, and finally filtering the micropolymers, washing the micropolymers with deionized water for several times, and then drying them at room temperature for standby use;
[0078] S6. The PET chips are heated to a molten state, and the micropolymer is surface-modified to make the micropolymer compatible with the PET chips. The micropolymer and the PET chips are mixed in a ratio of 8:1 to form a molten mixture. The molten mixture is filtered through a filter and then cooled to a temperature suitable for spinning to form a spinning solution, which is then wet-spun to obtain fibers.
[0079] Example 6
[0080] A method for preparing a light-absorbing and heat-generating regenerated polyester fiber material comprises the following steps:
[0081] S1, breaking the recycled plastic bottles into small pieces, using ethylene glycol as a reaction medium for depolymerization to obtain dimethyl terephthalate and ethylene glycol, carrying out an ester exchange reaction between dimethyl terephthalate and methanol, and then polymerizing the reaction to prepare fiber-grade recycled PET chips;
[0082] S2, using a mixed aqueous solution of aluminum isopropoxide, acetic acid and polyvinyl alcohol as a precursor solution, preparing a hybrid hierarchical porous material by freeze-drying technology, and then calcining at high temperature to remove organic matter, and finally obtaining a hierarchical porous γ-type alumina;
[0083] S3, immersing the hierarchical porous γ-alumina in a solution containing graphene, and uniformly dispersing the graphene into the pores of the porous γ-alumina by ultrasonic dispersion or high shear stirring to obtain a porous γ-alumina composite material doped with graphene, and then heat treating the porous γ-alumina composite material doped with graphene;
[0084] S4, adding a modifier to a urea-formaldehyde resin precursor solution, heating and stirring for 45 minutes, then adding 8% by mass of a porous γ-alumina composite material doped with graphene, and using a mechanical stirrer to stir the solution at a speed of 1600 rpm for 60 minutes to obtain a uniformly dispersed precursor mixed solution;
[0085] S5, heating paraffin to a molten state and mixing it with the precursor mixed solution, and using an emulsifier and a mechanical stirrer to form an emulsion, continuing to adjust the pH value by adding citric acid, heating the reaction system, and stirring the mechanical stirrer at a speed of 600 rpm for 110 min to obtain micropolymers, then adding sodium hydroxide solution to adjust the pH value to neutral, terminating the reaction, and finally filtering the micropolymers, washing the micropolymers with deionized water for several times, and then drying them at room temperature for standby use;
[0086] S6. The PET chips are heated to a molten state, and the micropolymer is surface-modified to make the micropolymer compatible with the PET chips. The micropolymer and the PET chips are mixed in a ratio of 8:1 to form a molten mixture. The molten mixture is filtered through a filter and then cooled to a temperature suitable for spinning to form a spinning solution, which is then wet-spun to obtain fibers.
[0087] Example 7
[0088] A method for preparing a light-absorbing and heat-generating regenerated polyester fiber material comprises the following steps:
[0089] S1, breaking the recycled plastic bottles into small pieces, using ethylene glycol as a reaction medium for depolymerization to obtain dimethyl terephthalate and ethylene glycol, carrying out an ester exchange reaction between dimethyl terephthalate and methanol, and then polymerizing the reaction to prepare fiber-grade recycled PET chips;
[0090] S2, using a mixed aqueous solution of aluminum isopropoxide, acetic acid and polyvinyl alcohol as a precursor solution, preparing a hybrid hierarchical porous material by freeze-drying technology, and then calcining at high temperature to remove organic matter, and finally obtaining a hierarchical porous γ-type alumina;
[0091] S3, immersing the hierarchical porous γ-alumina in a solution containing graphene, and uniformly dispersing the graphene into the pores of the porous γ-alumina by ultrasonic dispersion or high shear stirring to obtain a porous γ-alumina composite material doped with graphene, and then heat treating the porous γ-alumina composite material doped with graphene;
[0092] S4, adding a modifier to a urea-formaldehyde resin precursor solution, heating and stirring for 30 minutes, then adding 6% by mass of a porous γ-alumina composite material doped with graphene, and using a mechanical stirrer to stir the solution at a speed of 1200 rpm for 50 minutes to obtain a uniformly dispersed precursor mixed solution;
[0093] S5, heating paraffin to a molten state and mixing it with the precursor mixed solution, and using an emulsifier and a mechanical stirrer to form an emulsion, continuing to adjust the pH value by adding citric acid, heating the reaction system, and stirring the mechanical stirrer at a speed of 650 rpm for 115 minutes to obtain a micropolymer, wherein the weight ratio of paraffin, emulsifier, and citric acid is 25:5:0.8, then adding sodium hydroxide solution to adjust the pH value to neutral, terminating the reaction, and finally filtering the micropolymer, and washing the micropolymer with deionized water for several times, and then drying it at room temperature for standby use;
[0094] S6. The PET chips are heated to a molten state, and the micropolymer is surface-modified to make the micropolymer compatible with the PET chips. The micropolymer and the PET chips are mixed in a ratio of 8:1 to form a molten mixture. The molten mixture is filtered through a filter and then cooled to a temperature suitable for spinning to form a spinning solution, which is then wet-spun to obtain fibers.
[0095] Example 8
[0096] A method for preparing a light-absorbing and heat-generating regenerated polyester fiber material comprises the following steps:
[0097] S1, breaking the recycled plastic bottles into small pieces, using ethylene glycol as a reaction medium for depolymerization to obtain dimethyl terephthalate and ethylene glycol, carrying out an ester exchange reaction between dimethyl terephthalate and methanol, and then polymerizing the reaction to prepare fiber-grade recycled PET chips;
[0098] S2, using a mixed aqueous solution of aluminum isopropoxide, acetic acid and polyvinyl alcohol as a precursor solution, preparing a hybrid hierarchical porous material by freeze-drying technology, and then calcining at high temperature to remove organic matter, and finally obtaining a hierarchical porous γ-type alumina;
[0099] S3, immersing the hierarchical porous γ-alumina in a solution containing graphene, and uniformly dispersing the graphene into the pores of the porous γ-alumina by ultrasonic dispersion or high shear stirring to obtain a porous γ-alumina composite material doped with graphene, and then heat treating the porous γ-alumina composite material doped with graphene;
[0100] S4, adding a modifier to a urea-formaldehyde resin precursor solution, heating and stirring for 30 minutes, then adding 6% by mass of a porous γ-alumina composite material doped with graphene, and using a mechanical stirrer to stir the solution at a speed of 1200 rpm for 50 minutes to obtain a uniformly dispersed precursor mixed solution;
[0101] S5, heating paraffin to a molten state and mixing it with the precursor mixed solution, and using an emulsifier and a mechanical stirrer to form an emulsion, continuing to adjust the pH value by adding citric acid, heating the reaction system, and stirring the mechanical stirrer at a speed of 650 rpm for 115 minutes to obtain a micropolymer, wherein the weight ratio of paraffin, emulsifier, and citric acid is 30:7:1, then adding sodium hydroxide solution to adjust the pH value to neutral, terminating the reaction, and finally filtering the micropolymer, and washing the micropolymer with deionized water for several times, and then drying it at room temperature for standby use;
[0102] S6, heating the PET chips to a molten state, and performing surface modification on the micropolymer to make the micropolymer compatible with the PET chips to form a molten mixture, filtering the molten mixture through a filter and cooling it to a temperature suitable for spinning to form a spinning solution, and then obtaining fibers by wet spinning.
[0103] Example 9
[0104] A method for preparing a light-absorbing and heat-generating regenerated polyester fiber material comprises the following steps:
[0105] S1, breaking the recycled plastic bottles into small pieces, using ethylene glycol as a reaction medium for depolymerization to obtain dimethyl terephthalate and ethylene glycol, carrying out an ester exchange reaction between dimethyl terephthalate and methanol, and then polymerizing the reaction to prepare fiber-grade recycled PET chips;
[0106] S2, using a mixed aqueous solution of aluminum isopropoxide, acetic acid and polyvinyl alcohol as a precursor solution, preparing a hybrid hierarchical porous material by freeze-drying technology, and then calcining at high temperature to remove organic matter, and finally obtaining a hierarchical porous γ-type alumina;
[0107] S3, immersing the hierarchical porous γ-alumina in a solution containing graphene, and uniformly dispersing the graphene into the pores of the porous γ-alumina by ultrasonic dispersion or high shear stirring to obtain a porous γ-alumina composite material doped with graphene, and then heat treating the porous γ-alumina composite material doped with graphene;
[0108] S4, adding a modifier to a urea-formaldehyde resin precursor solution, heating and stirring for 40 minutes, then adding 6% by mass of a porous γ-alumina composite material doped with graphene, and using a mechanical stirrer to stir the solution at a speed of 1200 rpm for 50 minutes to obtain a uniformly dispersed precursor mixed solution;
[0109] S5, heating paraffin to a molten state and mixing it with the precursor mixed solution, and using an emulsifier and a mechanical stirrer to form an emulsion, continuing to adjust the pH value by adding citric acid, heating the reaction system, and stirring the mechanical stirrer at a speed of 650 rpm for 115 minutes to obtain a micropolymer, wherein the weight ratio of paraffin, emulsifier, and citric acid is 35:9:1.2, then adding sodium hydroxide solution to adjust the pH value to neutral, terminating the reaction, and finally filtering the micropolymer, and washing the micropolymer with deionized water for several times, and then drying it at room temperature for standby use;
[0110] S6. The PET chips are heated to a molten state, and the micropolymer is surface-modified to make the micropolymer compatible with the PET chips. The micropolymer and the PET chips are mixed in a ratio of 8:1 to form a molten mixture. The molten mixture is filtered through a filter and then cooled to a temperature suitable for spinning to form a spinning solution, which is then wet-spun to obtain fibers.
[0111] Comparative Example 1
[0112] The difference from Example 1 is that step S2 and step S3 are removed, and step S4 is changed to taking a urea-formaldehyde resin precursor solution and adding melamine, and heating and stirring for 40 minutes, and using a mechanical stirrer to stir the solution at a speed of 1200 rpm for 50 minutes to obtain a uniformly dispersed precursor mixed solution.
[0113] Comparative Example 2
[0114] The difference from Example 1 is that: step S2 and step S3 are removed, and step S4 is changed to disperse graphene oxide in deionized water to form a uniform suspension, take a urea-formaldehyde resin precursor solution, add melamine and the suspension, use a mechanical stirrer to stir the solution at a speed of 1200 rpm for 50 minutes to obtain a uniformly dispersed precursor mixed solution, heat to 90°, react for 1 hour, and then cool for use.
[0115] The light-absorbing, heat-generating regenerated polyester fibers prepared in Examples 1-9 and Comparative Examples 1-2 of the present application were subjected to performance tests.
[0116] The fiber was subjected to comparative tests under outdoor sunlight and far-infrared light, and the results are shown in the following table:
[0117] Table 1
[0118] Test products Outdoor sunlight exposure for 4 minutes Outdoor sunlight for 10 minutes Far infrared light 10min <![CDATA[ 对比例1 ]]> <![CDATA[ 27 °]]> <![CDATA[ 32 °]]> <![CDATA[ 31 °]]> <![CDATA[ 对比例2 ]]> <![CDATA[ 28 °]]> <![CDATA[ 33 °]]> <![CDATA[ 32 °]]> <![CDATA[ 实施例1 ]]> <![CDATA[ 29 °]]> <![CDATA[ 34 °]]> <![CDATA[ 33 °]]> <![CDATA[ 实施例2 ]]> <![CDATA[ 33 °]]> <![CDATA[ 39 °]]> <![CDATA[ 38 °]]> <![CDATA[ 实施例3 ]]> <![CDATA[ 31 °]]> <![CDATA[ 36 °]]> <![CDATA[ 35.5 °]]> <![CDATA[ 实施例4 ]]> <![CDATA[ 30 °]]> <![CDATA[ 35 °]]> <![CDATA[ 35 ° <!-- 8 -->]]> <![CDATA[ 实施例5 ]]> <![CDATA[ 30 °]]> <![CDATA[ 36 °]]> <![CDATA[ 35 °]]> <![CDATA[ 实施例6 ]]> <![CDATA[ 31 °]]> <![CDATA[ 36 °]]> <![CDATA[ 35 °]]> <![CDATA[ 实施例7 ]]> <![CDATA[ 30 °]]> <![CDATA[ 35 °]]> <![CDATA[ 34.5 °]]> <![CDATA[ 实施例8 ]]> <![CDATA[ 30 °]]> <![CDATA[ 35 °]]> <![CDATA[ 35 °]]> <![CDATA[ 实施例9 ]]> <![CDATA[ 30 °]]> <![CDATA[ 34 °]]> <![CDATA[ 34 °]]>
[0119] It can be seen from the results shown in Examples 1-9 and Comparative Examples 1-2 of the present application that the porous γ-type alumina composite material doped with graphene used in the present application as the shell of the micropolymer enhances the heat conduction efficiency and improves the photothermal conversion efficiency of the fiber. The present application uses titanium dioxide and fiber-grade recycled PET chips for melt blending, which can give full play to the light absorption and heat generation function of the photothermal powder and improve the tensile strength and modulus of the fiber-grade recycled PET chips.
[0120] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a light-absorbing and heat-generating regenerated polyester fiber material, characterized in that: The following steps are involved: S1, breaking the recycled plastic bottles into small pieces, using ethylene glycol as a reaction medium for depolymerization to obtain dimethyl terephthalate and ethylene glycol, carrying out an ester exchange reaction between dimethyl terephthalate and methanol, and then polymerizing the reaction to prepare fiber-grade recycled PET chips; S2, using a mixed aqueous solution of aluminum isopropoxide, acetic acid and polyvinyl alcohol as a precursor solution, preparing a hybrid hierarchical porous material by freeze-drying technology, and then calcining at high temperature to remove organic matter, and finally obtaining a hierarchical porous γ-type alumina; S3, immersing the hierarchical porous γ-alumina in a solution containing graphene, and uniformly dispersing the graphene into the pores of the porous γ-alumina by ultrasonic dispersion or high shear stirring to obtain a porous γ-alumina composite material doped with graphene, and then heat treating the porous γ-alumina composite material doped with graphene; S4, adding a modifier to a urea-formaldehyde resin precursor solution, heating and stirring for 30-45 minutes, then adding a certain mass fraction of a porous γ-alumina composite material doped with graphene, and using a mechanical stirrer to stir the solution at a speed of 300 to 2000 rpm for 30-60 minutes to obtain a uniformly dispersed precursor mixed solution; S5, heating the paraffin to a molten state and mixing it with the precursor mixed solution, and using an emulsifier and a mechanical stirrer to form an emulsion, continuing to adjust the pH value by adding a pH regulator, heating the reaction system, and stirring the mechanical stirrer at a speed of 600-700 rpm for 110-125 min to obtain a micropolymer solution, then adding a pH regulator to adjust the pH value of the micropolymer solution to neutral, terminating the reaction, and finally filtering the micropolymer, and washing the micropolymer with deionized water for several times, and then drying it at room temperature for standby use; S6. The fiber-grade recycled PET chips are heated to a molten state, and the micropolymers are surface-modified to make the micropolymers compatible with the PET chips to form a molten mixture. The molten mixture is filtered through a filter and then cooled to a temperature suitable for spinning to form a spinning solution, which is then wet-spun to obtain fibers.
2. The method for preparing a light-absorbing and heat-generating regenerated polyester fiber material according to claim 1, characterized in that: The urea-formaldehyde resin precursor solution is prepared by dissolving urea and a formaldehyde solution with a concentration of 37% in a reactor, and the modifier is melamine.
3. The method for preparing a light-absorbing and heat-generating regenerated polyester fiber material according to claim 2, characterized in that: The urea-formaldehyde resin precursor solution is prepared by adding triethanolamine to adjust the pH value of the solution.
4. The method for preparing a light-absorbing and heat-generating regenerated polyester fiber material according to claim 1, characterized in that: In the step S3, the weight ratio of graphene to hierarchical porous γ-alumina is (1-3): (110-180).
5. The method for preparing a light-absorbing and heat-generating regenerated polyester fiber material according to claim 1, characterized in that: The graphene solution in S3 is prepared by the following steps: (1) Oxidizing graphite to obtain graphene oxide by Hummers method; (2) removing oxygen-containing groups of graphene oxide by chemical reduction to obtain reduced graphene oxide; (3) The reduced graphene oxide powder is added to a solvent and subjected to a long-term ultrasonic treatment using an ultrasonic processor.
6. The method for preparing a light-absorbing and heat-generating regenerated polyester fiber material according to claim 1, characterized in that: The mass fraction of the graphene-doped porous gamma-alumina composite material relative to the micropolymer is 1%-8%.
7. The method for preparing a light-absorbing and heat-generating regenerated polyester fiber material according to claim 1, characterized in that: In step S5, the weight ratio of paraffin wax, emulsifier and citric acid is (20-40): (3-10): (0.3-1.8).
8. The method for preparing a light-absorbing and heat-generating regenerated polyester fiber material according to claim 1, characterized in that: The paraffin is replaced by one or more of nano zirconium carbide, polyethylene glycol, hydrocarbon wax and carbon nanotubes.
9. The method for preparing a light-absorbing and heat-generating regenerated polyester fiber material according to claim 1, characterized in that: The molten mixture filtered in step S6 is melted by a screw extruder and quantitatively fed into a spinning assembly through a spinning pump, and then extruded from the capillaries of a spinneret to form liquid filaments, which are then cooled and formed, stretched into filaments at high speed by a winding device, and then heat-set to obtain fibers.
10. The method for preparing a light-absorbing and heat-generating regenerated polyester fiber material according to claim 1, wherein the fiber-grade regenerated PET slices in step S6 are melt-blended with titanium dioxide and then combined with the micropolymer.
Citation Information
Patent Citations
A modified polyester fiber and its preparation method
CN110552081B
Preparation method of graphene enhanced polyester fibers
CN107988650A
Graphene reinforced polyethylene terephthalate
CN108350210A
Preparation process and equipment for improving strength of polyester staple fibers
CN114481345A
Preparation method of Al2O3 / graphene synergistically modified carbon fiber / epoxy resin composite material
CN117327372A